Cognitive and health profile of elderly of a Coexistence Center (Research, Society and Development, 2021)
Objective: To identify the cognitive profile and health conditions of elderly participants in a Living Center for the Elderly in the city of Campina Grande/PB. Methodology: This is a descriptive and cross-sectional study with a quantitative approach. A sociodemographic questionnaire and the Mini Mental State Examination were used as a data collection instrument. For data  analysis, descriptive statistics was used. Results: There was a predominance of females 60.7%, aged between 70 and 79 years old 35.7%, widowers 44.7%, one to four years of schooling 53.6%, 83.9% lived together. Regarding self-reported morbidities, systemic arterial hypertension and diabetes mellitus stood out. Through the Mini Mental State Examination it was found that 44.6% of the elderly presented cognitive decline when analyzing the total group, being more predominant in women. Conclusions: It is hoped that these results support professionals and scholars in the field of gerontology, with respect to the characterization of the sociodemographic and cognitive profile of elderly participants in Community Centers, and that it also helps in planning activities and professional monitoring.